Managing Pandemics with Health Informatics - Dixon, Brian E.; Holmes, John H.; Section Editors for the IMIA Yearbook Section on Managing Pandemics with Health Informatics (Yearbook of Medical Informatics, 2021)
Objective: To summarize significant research contributions on managing pandemics with health informatics published in 2020.Methods: An extensive search using PubMed and Scopus was conducted to identify peer-reviewed articles published in 2020 that examined health informatics systems used during the global COVID-19 pandemic. The selection process comprised three steps: 1) 15 candidate best papers were first selected by the two section editors; 2) external reviewers from internationally renowned research teams reviewed each candidate best paper; and 3) the final selection of three best papers was conducted by the editorial committee of the International Medical Informatics Association (IMIA) Yearbook.Results: Selected best papers represent the important and diverse ways that health informatics supported clinical and public health responses to the global COVID-19 pandemic. Selected papers represent four groups of papers: 1) Use of analytics to screen, triage, and manage patients; 2) Use of telehealth and remote monitoring to manage patients and populations; 3) Use of EHR systems and administrative systems to manage internal operations of a hospital or health system; and 4) Use of informatics methods and systems by public health authorities to capture, store, manage, and visualize population-level data and information.Conclusion: Health informatics played a critical role in managing patients and populations during the COVID-19 pandemic. Health care and public health organizations both leveraged available information systems and standards to rapidly identify cases, triage infected individuals, and monitor population trends. The selected best papers represent a fraction of the body of knowledge stemming from COVID-19, most of which is focused on pandemic response. Future work will be needed to help the world recover from the pandemic and strengthen the health information infrastructure in preparation for the next pandemic.
Keywords: Pandemics; COVID-19; public health informatics; medical informatics